2016
DOI: 10.1097/md.0000000000002532
|View full text |Cite|
|
Sign up to set email alerts
|

Polysplenia Syndrome With Splenic and Skeletal Muscle Metastases From Thyroid Carcinoma Evaluated by FDG PET/CT

Abstract: Polysplenia syndrome (PSS) is a rare congenital abnormality. Metastases to spleen and skeletal muscle from differentiated thyroid cancer (DTC) are also extremely rare. Our case report aims to present an interesting case of PSS associated with splenic metastasis (SM) and skeletal muscle metastasis (SMM) from advanced papillary thyroid carcinoma which was evaluated on fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT).An 84-year-old Chinese man was admitted with the history of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Cassidy et al ( 18 ) reported a case of PTC muscle metastasis; they reported 3 documented cases of symptomatic PTC muscle metastasis, and 3 cases of incidentally diagnosed PTC by single-photon emission computed tomography/CT and PET/CT, from the literature. In 2016, Li et al ( 19 ) discussed a case of synchronous PTC skeletal muscle metastasis and stated that there were ‘only a few reports’ of DTC skeletal muscle metastasis, without precise descriptions. Kuscic et al ( 20 ) published a case of PTC muscle metastasis and undertook a retrospective review of the literature, identifying only 7 reports of PTC muscle metastasis, with reference to studies by Song et al ( 5 ) and Iwai et al ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cassidy et al ( 18 ) reported a case of PTC muscle metastasis; they reported 3 documented cases of symptomatic PTC muscle metastasis, and 3 cases of incidentally diagnosed PTC by single-photon emission computed tomography/CT and PET/CT, from the literature. In 2016, Li et al ( 19 ) discussed a case of synchronous PTC skeletal muscle metastasis and stated that there were ‘only a few reports’ of DTC skeletal muscle metastasis, without precise descriptions. Kuscic et al ( 20 ) published a case of PTC muscle metastasis and undertook a retrospective review of the literature, identifying only 7 reports of PTC muscle metastasis, with reference to studies by Song et al ( 5 ) and Iwai et al ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present case, the RDM locations included liver, pancreas, kidney, parotid gland, salivary gland, multiple skeletal muscles, and subcutaneous tissues. Generally, locations of simultaneous multiple RDMs do not exceed three (10, 11, 18–23). Interestingly, in the present case, pathologically confirmed RDMs locations from PTC were six.…”
Section: Discussionmentioning
confidence: 99%
“…The other seven cases reported as skeletal muscle metastasis associated with other sites are usually combined with lung metastasis [9,11,13,15]. The most common skeletal metastasis site appears to be the erector spinae [14][15][16]19] and thigh muscle group [10][11][12][13]. Unique cases of muscle metastasis sites were reported localized in trapezoid [17], arm biceps [18], deltoid [7], gastrocnemius [9], and rectus abdominis [20] muscles.…”
Section: The Available Evidence Of the Existing Casesmentioning
confidence: 99%